A Comprehensive Systematic Review of The Relationship between Body Mass Index and The Risk of Implant Failure in Total Knee Arthroplasty - Satya Agung Nugroho; Nazalla Gwen Vaganesha; Agus Saribudaya (International Medical Journal Corp. Ltd, 2022)
Introduction: Total knee arthroplasty (TKA) is a highly successful procedure for end-stage knee osteoarthritis. However, the global rise in obesity presents a significant challenge, as elevated body mass index (BMI) is a suspected risk factor for postoperative complications, particularly implant failure. This systematic review aims to synthesize the existing evidence on the relationship between BMI and the risk of implant failure following primary TKA. Methods: A systematic review of the literature was conducted following established guidelines. Eighty studies meeting predefined inclusion criteria were selected from 118 screened sources. Inclusion criteria focused on adult primary TKA patients, availability of BMI data, reported implant failure outcomes, and a minimum follow-up of 6 months. Data extraction covered study design, BMI categories, population characteristics, definitions of implant failure, follow-up duration, effect measures, and confounding factors. Results: The evidence demonstrates a clear dose-response relationship between increasing BMI, particularly at levels ≥40 kg/m², and elevated risk of all-cause revision and infection-related failure. Meta-analyses indicate risk ratios (RR) for all-cause revision rise from 1.19 for severe obesity (BMI ≥35) to 4.75 for super-obesity (BMI ≥50) (Chaudhry et al., 2019). Septic revision risk shows an even stronger association, with RR reaching 3.69 for morbid obesity (BMI ≥40) (Chaudhry et al., 2019). In contrast, the association between BMI and aseptic loosening is inconsistent and generally non-significant. Some studies employing specific implant designs or surgical techniques reported no significant survival differences across BMI groups (Gaillard et al., 2017; Kanna et al., 2021). Discussion: The relationship between BMI and TKA failure is nuanced, primarily driven by a markedly increased risk of periprosthetic joint infection (PJI) rather than mechanical failure. Reconciling heterogeneous findings requires consideration of BMI threshold effects, failure type specificity, implant/technique considerations, and follow-up duration. The risk appears most clinically significant at BMI ≥40 kg/m². While obesity elevates complication risks, patients across all BMI categories achieve meaningful functional improvements post-TKA. Conclusion: Elevated BMI, especially morbid and super-obesity, is a significant risk factor for implant failure, predominantly through infectious complications. This should inform preoperative counselling and risk stratification. However, obesity should not be an absolute contraindication for TKA. Future strategies should emphasize optimized surgical techniques, targeted infection prophylaxis, and structured preoperative weight management programs for high-risk patients to improve long-term outcomes.